Evaluating Rates of Recurrent Ischemic Stroke Among Young Adults With Embolic Stroke of Undetermined Source: The Young ESUS Longitudinal Cohort Study - Perera, Kanjana S; de Sa Boasquevisque, Danielle; Rao-Melacini, Purnima; Taylor, Amanda; Cheng, Anna; Hankey, Graeme J; Lee, Sarah; Fabregas, Joan Marti; Ameriso, Sebastian F; Field, Thalia S; Arauz, Antonio; Coutts, Shelagh B; et al. (JAMA neurology, 2022)
IMPORTANCE: Cryptogenic strokes constitute approximately 40% of ischemic strokes in young adults, and most meet criteria for the embolic stroke of undetermined source (ESUS). Two randomized clinical trials, NAVIGATE ESUS and RESPECT ESUS, showed a high rate of stroke recurrence in older adults with ESUS but the prognosis and prognostic factors among younger individuals with ESUS is uncertain. OBJECTIVE: To determine rates of and factors associated with recurrent ischemic stroke and death and new-onset atrial fibrillation (AF) among young adults. DESIGN, SETTING, AND PARTICIPANTS: This multicenter longitudinal cohort study with enrollment from October 2017 to October 2019 and a mean follow-up period of 12 months ending in October 2020 included 41 stroke research centers in 13 countries. Consecutive patients 50 years and younger with a diagnosis of ESUS were included. Of 576 screened, 535 participants were enrolled after 1 withdrew consent, 41 were found to be ineligible, and 2 were excluded for other reasons. The final follow-up visit was completed by 520 patients. MAIN OUTCOMES AND MEASURES: Recurrent ischemic stroke and/or death, recurrent ischemic stroke, and prevalence of patent foramen ovale (PFO). RESULTS: The mean (SD) age of participants was 40.4 (7.3) years, and 297 (56%) participants were male. The most frequent vascular risk factors were tobacco use (240 patients [45%]), hypertension (118 patients [22%]), and dyslipidemia (109 patients [20%]). PFO was detected in 177 participants (50%) who had transthoracic echocardiograms with bubble studies. Following initial ESUS, 468 participants (88%) were receiving antiplatelet therapy, and 52 (10%) received anticoagulation. The recurrent ischemic stroke and death rate was 2.19 per 100 patient-years, and the ischemic stroke recurrence rate was 1.9 per 100 patient-years. Of the recurrent strokes, 9 (64%) were ESUS, 2 (14%) were cardioembolic, and 3 (21%) were of other determined cause. AF was detected in 15 participants (2.8%; 95% CI, 1.6-4.6). In multivariate analysis, the following were associated with recurrent ischemic stroke: history of stroke or transient ischemic attack (hazard ratio, 5.3; 95% CI, 1.8-15), presence of diabetes (hazard ratio, 4.4; 95% CI, 1.5-13), and history of coronary artery disease (hazard ratio, 10; 95% CI, 4.8-22). CONCLUSIONS AND RELEVANCE: In this large cohort of young adult patients with ESUS, there was a relatively low rate of subsequent ischemic stroke and a low frequency of new-onset AF. Most recurrent strokes also met the criteria for ESUS, suggesting the need for future studies to improve our understanding of the underlying stroke mechanism in this population.
Keywords: Embolic Stroke; Humans; Longitudinal Studies; foramen ovale apertum; Stroke; kohortové studie; Female; rizikové faktory; mladý dospělý; dospělí; Aged; senioři; embolická cévní mozková příhoda; lidé; Foramen Ovale, Patent; Cohort Studies; Ischemic Stroke; cévní mozková příhoda; Adult; ženské pohlaví; longitudinální studie; Male; ischemická cévní mozková příhoda; Young Adult; mužské pohlaví; Risk Factors